2009
DOI: 10.1002/dvdy.22028
|View full text |Cite
|
Sign up to set email alerts
|

Diversification of the expression patterns and developmental functions of the dishevelled gene family during chordate evolution

Abstract: Dishevelled (Dvl) proteins are key transducers of Wnt signaling encoded by members of a multi-gene family in vertebrates. We report here the divergent, tissue-specific expression patterns for all three Dvl genes in Xenopus embryos, which contrast dramatically with their expression patterns in mice. Moreover, we find that the expression patterns of Dvl genes in the chick diverge significantly from those of Xenopus. In addition, in hemichordates, an outgroup to chordates, we find that the one Dvl gene is dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 78 publications
3
48
0
Order By: Relevance
“…For the TP53 gene family, one common ancestral gene has been identified in the unduplicated ancestor B. floridae (Putnam et al, 2008) and three TP53 gene family members have been found in most vertebrates (Yang et al, 2002;Nedelcu and Tan 2007). In a similar way, a single DVL ancestral gene has been identified in C. intestinalis and three DVL gene family members has been reported in vertebrates (Gray et al, 2009). These data could be interpreted to mean that one ancestral gene gave rise to four paralogs after 2R, but one gene has been lost after the second duplication.…”
Section: The Evolutionary Origin Of Multiple Ss In Vertebrates Revealmentioning
confidence: 85%
“…For the TP53 gene family, one common ancestral gene has been identified in the unduplicated ancestor B. floridae (Putnam et al, 2008) and three TP53 gene family members have been found in most vertebrates (Yang et al, 2002;Nedelcu and Tan 2007). In a similar way, a single DVL ancestral gene has been identified in C. intestinalis and three DVL gene family members has been reported in vertebrates (Gray et al, 2009). These data could be interpreted to mean that one ancestral gene gave rise to four paralogs after 2R, but one gene has been lost after the second duplication.…”
Section: The Evolutionary Origin Of Multiple Ss In Vertebrates Revealmentioning
confidence: 85%
“…This does not exclude overlapping functions in CE movements or other developmental processes in general, as reported for Dvl2 and Dvl3 in CE movements (Tadjuidje et al. , 2011) and for Dvl1 and Dvl2 in neural crest migration (Gray et al. , 2009), since these morphogenetic processes are regulated by multiple interacting Wnt pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Although the fly displays only a single Dishevelled protein (Dsh), higher-order species express several isoforms of Dvl. Mammalian cells express three isoforms, Dvl1, Dvl2, and Dvl3; each isoform is expressed at varying levels (Sussman et al, 1994;Klingensmith et al, 1996;Gray et al, 2009). Targeted gene disruptions performed in mice (Lijam et al, 1997;Hamblet et al, 2002;Etheridge et al, 2008) as well as knockdown and rescue protocols performed in mouse F9 cells (Lee et al, 2008) demonstrate that mammalian Dvl proteins are not truly 'redundant' with respect to function.…”
Section: Discussionmentioning
confidence: 99%